The benefit and impact of e-commerce in tourism enterprises - Yousef A. Baker, El-Ebiary; Mohd Hafiz, Yusoff@Che Abdullah; Pathmanathan, P.R.; Khairi, Aseh; Omar Mohammed Ali, Abdullah Al-Qudah; Bishwajeet, Pande; Waheeb, Abu-Ulbeh; Yazeed, Al Moaiad; Samer, Bamansoor (2021)
It is generally accepted that the advancement of information and communication technology (ICT) has contributed to the exponential growth of the electronic marketplace. ICT, especially the internet, is believed to be the most cost-effective tool to help brick and mortar companies gain greater markets and the opportunity to compete with other competitive organizations in attracting consumers to their goods, services and knowledge with the strong waves of globalization and liberalization around the world. Nowadays, technology is developing and making our world borderless and infinite. E - commerce is one of the innovations that is transforming the demand for businesses. Electronic commerce ( e - commerce ) is considered to be an effective method for promoting, selling and incorporating online services that can play an important role in customer recognition, acquisition and maintenance. Through the e - commerce site, people can also promote services, replacing the conventional process, which is cheaper and more efficient. There is a set of effective organizational and external organizational variables in e - commerce that should be taken into consideration. The aim of this study is to suggest an e - commerce solution that can solve the problem for tourism companies. The paper focuses on Malaysia's tourism industry and focuses only on the angle of e - commerce adoption management.